-6x-3 2 2x-32x+3 3-2x Если можно в подробностях



-6x-3                                     2       

(2x-3)(2x+3)                        3-2x

 

 

Если можно в подробностях.

 

 

  • ===============================================
  • -6х-3                2      -6х-3                  2      -6х-3+4х+6     -2х+3            -(2х-3)
    __________ -____ = ___________ + ____ = _________=__________ = _________=
    (2х-3)(2х+3)  3-2х     (2з-3)(2х+3)      2х-3    (2х-3)(2х+3) (2х-3)(2х+3)   (2х-3)(2х+3)

         -1
    = _____
       2х+3